Estrategias Tácticas y Turismo Social para adultos mayores de la ciudad de Babahoyo - Ramos Rodríguez, Joselin Nicela (2021)
There is no specific definition for tactical strategies, but we can define strategies as programs that assume commitments of emphasis and resources to implement a basic mission, it has been visualized that one of the strategies that feasible results in this case study would be the strategy of marketing since it is seeking to know the needs of an organization and in this case it would help a lot to promote the public and private entities that would be willing to help in social tourism for the elderly in the Babahoyo canton. Social tourism is linked to tourist activity, it is aimed at people who have less favorable conditions to be able to travel either due to their low purchasing power, physical or mental disabilities and their low economy, in this case study the beneficiaries will be older adults than with the implementation of tactical strategies and recreational activities.